Obviously : stories from my timeline - Hughes, Akilah, 1989- (Razorbill, 2019)
"Comedian and activist Akilah Hughes shares everything about her journey from a childhood in the south to the big screen while dispensing invaluable big-sister-style advice to a generation of future YouTubers"--